Implementasi Nilai-Nilaiajaran Tri Kaya Parisuddha Pada Siswa Hindu Di SDN Balun 1 Lamongan Jawa Timur - Tiara Krisna Widya Dharma; I Wayan Darna; I Made Wirahadi Kusuma (Jurnal Penelitian Agama Hindu, 2019)
SDN Balun 1 is a public elementary school (not SD Hindu) so students there have a homogeneous religion. Nevertheless Hinduism education still exists but is very minimal because indeed students who embrace Hinduism are also very few and Hindu Religious Education teachers also lack time to teach Hindu Religious Education as a whole. So that human behaviors that are contrary to the rules of religion seem to be caused by several factors. One of the anarchic movements in some areas, acts of drunkenness, brawls, use of alcohol and illegal drugs among the younger generation. In fostering human attitudes and behavior itself, there needs to be guidance through self-control both words, deeds and thoughts. The three teachings provide a guide so that humans in the movement of thoughts, words and deeds are always controlled and controlled for the sake of creating harmony in life. The theory used is cognitive learning theory, constructive learning theory and behavior change theory. This type of research is qualitative research, the type of data this research is qualitative data and data sources are primary data and secondary data. Data was collected with observation techniques, interview techniques, library techniques and documentation techniques. Furthermore, the data is analyzed by reducing data and drawing conclusions. Based on the data analysis, the results were obtained, among others, the pattern of learning Hinduism in Balun 1 Lamongan Elementary School is using the Sad Dharma method in its learning, the implementation of Tri Kaya Parisuddha teaching values carried out in the teaching and learning activities of Hinduism lessons, student discipline, habituation, implementation of environmental hygiene. So that the perceived benefits are changes in behavior perceived by students and the creation of religious harmony in schools and in the community.